Suicide tree poisoning - A., Shivaraja; Appaji, Shruti; V. R., Sudha Reddy (International Journal of Contemporary Pediatrics, 2018)
Poisoning accounts to 0.33-7.6% paediatric emergency admissions, which are accidental or unintentional. Yellow oleander, an ornamental plant with a scientific name “Thevetia peruviana”. All the parts of the tree are poisonous hence, known as “Suicide Tree”. Trees are easily accessible and swallowing of seeds which are the most toxic, is the preferred mode of intentional poisoning in South India. Ingestion of one seed is equivalent to 100 digoxin tablets. The phytotoxins of the plant can cause local gastric irritation and severe cardiotoxic manifested as arrhythmias, conduction defects which if left untreated is fatal. Management includes gastric decontamination, specific antidotes anti-digoxin Fab and Fructose 1,6 diphosphate administration, cardioversion and cardiovascular supportive care. Here, authors report an adolescent female presenting with sinus bradycardia following intentional consumption of the yellow oleander seeds.